Soil moisture and pH differentially drive arbuscular mycorrhizal fungal composition in the riparian zone along an alpine river of Nam Co watershed - Zhou, Yaxing; Chen, Keyu; Muneer, Muhammad Atif; Li, Congcong; Shi, Hailan; Tang, Yu; Zhang, Jing; Ji, Baoming (Frontiers in Microbiology, 2022)
Riparian zone is an important ecological corridor between the upstream and downstream rivers. Its highly complex biological and physical environments significantly affect the biogeographical pattern of species and various ecosystem functions. However, in alpine riparian ecosystems, the distribution patterns and drivers of arbuscular mycorrhizal (AM) fungi, a group of functionally important root-associated microorganisms, remain poorly understood. We investigated the AM fungal diversity and community composition in near-bank (wetland) and far-bank (alpine meadows) soils along the Niaqu River in the Nam Co watershed, , and the geographic distance, plant community characteristics and abiotic factors shaping these distributions. Overall, 184 OTUs were identified in the riparian ecosystem, predominantly belonging to the genus Glomus, especially in the downstream soils, and Claroideoglomus in near-bank soils. AM fungal abundance and α diversity showed an overall increasing trend along the river, while the extraradical hyphae declined dramatically from the middle of the river. AM fungal communities significantly varied between the wetland and alpine meadows in the riparian zone, mainly driven by the geographic distance, soil water content, soil pH, and plant communities. Specifically, soil pH was the principal predictor of AM fungal community in near-bank wetland soils, while soil water content had a most substantial direct effect in alpine meadows. These findings indicate that abiotic factors are the most important divers in shaping AM fungal communities at the watershed scale, which could be helpful in alpine riparian biodiversity conservation and management.